Retracts in equiconnected spaces. (1993) - Kwak, Jin Ho; Lee, Jaeun
Abstract : The object of this paper is to show that the concepts retract and strong deformation retract coincide for a subset of an equiconnected space. Also, we have a similar local version in a locally equiconnected space.